Pretreatment methods for lignocellulosic biofuels production: Current advances, challenges and future prospects - Cheah, Wai Yan (Animo Repository, 2020)
Lignocellulosic biomass has been recognized as promising feedstock for biofuels production. However, the high cost of pretreatment is one of the major challenges hindering large-scale production of biofuels from these abundant, indigenously-available, and economic feedstock. In addition to high capital and operation cost, high water consumption is also regarded as a challenge unfavorably affecting the pretreatment performance. In the present review, advances in lignocellulose pretreatment technologies for biofuels production are reviewed and critically discussed. Moreover, the challenges faced and future research needs are addressed especially in optimization of operating parameters and assessment of total cost of biofuel production from lignocellulose biomass at large scale by using different pretreatment methods. Such information would pave the way for industrial-scale lignocellulosic biofuels production. Overall, it is important to ensure that throughout lignocellulosic bioethanol production processes, favorable features such as maximal energy saving, waste recycling, wastewater recycling, recovery of materials, and biorefinery approach are considered. © 2020 BRTeam.